2010
DOI: 10.1007/s11103-010-9678-4
|View full text |Cite
|
Sign up to set email alerts
|

Chloramphenicol acetyltransferase as selectable marker for plastid transformation

Abstract: Chloroplast transformation remains a demanding technique and is still restricted to relatively few plant species. The limited availability of selectable marker genes and the lack of selection markers that would be universally applicable to all plant species represent some of the most serious technical problems involved in extending the species range of plastid transformation. Here we report the development of the chloramphenicol acetyltransferase gene cat as a new selectable marker for plastid transformation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 40 publications
3
35
0
Order By: Relevance
“…Plant 1Bs was heteroplasmic due to the presence of an additional 4.4 kb fragment typical of non-transformed plastome, while the presence of the 5.2 kb fragment and the absence of the 2.1 kb fragment in this plant indicated that the probe binding site on the trnA gene was missing or that the BglII site on the trnA gene was absent. The presence of the faint 4.5 kb fragment in the transplastomic plants 1Bg, 5Bg and 5Bs was likely due to plastid DNA inserted in the nuclear genome (Ayliffe and Timmis 1992;De Marchis et al 2011) or recombination between duplicated expression elements (the endogenous and the introduced prrn promoters) (Rogalski et al 2006;Li et al 2011). These results confirmed that plant 1Bs, besides being heteroplasmic, underwent a genetic rearrangement in the hemL-trnA region.…”
Section: Molecular Analysessupporting
confidence: 56%
See 2 more Smart Citations
“…Plant 1Bs was heteroplasmic due to the presence of an additional 4.4 kb fragment typical of non-transformed plastome, while the presence of the 5.2 kb fragment and the absence of the 2.1 kb fragment in this plant indicated that the probe binding site on the trnA gene was missing or that the BglII site on the trnA gene was absent. The presence of the faint 4.5 kb fragment in the transplastomic plants 1Bg, 5Bg and 5Bs was likely due to plastid DNA inserted in the nuclear genome (Ayliffe and Timmis 1992;De Marchis et al 2011) or recombination between duplicated expression elements (the endogenous and the introduced prrn promoters) (Rogalski et al 2006;Li et al 2011). These results confirmed that plant 1Bs, besides being heteroplasmic, underwent a genetic rearrangement in the hemL-trnA region.…”
Section: Molecular Analysessupporting
confidence: 56%
“…1), harboring both aadA and hemL, conferring spectinomycin and gabaculine resistance, respectively. This allowed us to perform a direct comparison between the two selections systems, an experimental design described in Li et al (2011) to demonstrate chloramphenicol selection for plastome transformation.…”
Section: Sensitivity Of Tobacco To Gabaculine and Plastome Transformamentioning
confidence: 99%
See 1 more Smart Citation
“…genes remains more technically challenging because it requires either recycling of the aadA marker, cotransformation with two plasmids, or sequential transformation using two different selection markers (supertransformation). Although aadA is the only marker gene that is routinely used in plastid transformation experiments, a few alternative selectable marker genes have become available (Carrer et al, 1993;Huang et al, 2002;Li et al, 2011), enabling us to employ a supertransformation approach to analyze the effects of the combined inactivation of two nonessential plastid ribosomal protein genes. To this end, we used the aphA-6 marker gene, which confers kanamycin resistance (Huang et al, 2002) to disrupt a second ribosomal protein gene in the rps15, rpl33, and rpl36 knockout plants that had previously been generated with the aadA marker (Rogalski et al, 2008;Fleischmann et al, 2011).…”
Section: Construction Of Transplastomic Double Knockout Plants For Thmentioning
confidence: 99%
“…The most commonly used selective marker gene is aadA, encoding spectinomycin resistance . Kanamycin (Carrer et al, 1993), chloramphenicol (Li et al, 2011), and the amino acid analogs 4-methylindole and 7-methyl-DL-Trp (Barone et al, 2009) have also been successfully employed as selective agents.…”
Section: The Technology Of Plastid Transformationmentioning
confidence: 99%